Comprehensive germline and somatic genomic profiles of Chinese patients with biliary tract cancer - Yu, Haipeng; Xu, Yan; Gao, Wei; Li, Mei; He, Ji’an; Deng, Xiaoqian; Xing, Wenge (Frontiers in Oncology, 2022)
Background: Biliary tract cancer (BTC) is an uncommon but highly lethal malignancy with poor clinical outcomes. To promote the development of precision medicine for BTC, uncovering its genomic profile becomes particularly important. However, studies on the genomic feature of Chinese BTC patients remain still insufficient. Methods: A total of 382 Chinese patients with BTC were enrolled in this study, including 71 with intrahepatic cholangiocarcinoma (ICC), 194 with extrahepatic cholangiocarcinoma (ECC), and 117 with gallbladder carcinoma (GBC). Genetic testing was performed by utilizing the next-generation sequencing (NGS) of 499 cancer-related genes and the results were compared to those of Western BTC patients (MSKCC cohorts). Results: The most prevalent genes were TP53 (51.6%), ARID1A (25.9%), KMT2C (24.6%), NCOR1 (17%), SMAD4 (15.2%), KRAS (14.9%), KMT2D (14.9%), ATM (14.1%), and APC (13.9%) in Chinese BTC patients. TP53, SMAD4, and APC was more prevalent in GBC, ECC, and ICC, respectively. In addition, 10.5% of Chinese BTC patients harbored pathogenic or likely pathogenic (P/LP) germline alterations in 41 genes, which were mainly related to DNA damage repair (DDR). Additionally, the genomic features of Chinese and Western BTC tumors were similar, with the exception of the notable difference in the prevalence of TP53, KRAS, IDH1, KMT2C, and SMAD4. Notably, Chinese BTC patients had high prevalence (57.1%) of actionable alterations, especially for those with ECC, and half (192/382) of them had somatic DDR alterations, with the prevalence of deleterious ones being significantly higher than their Western counterparts. 23.0% of patients had a higher tumor mutational burden (TMB-H, over 10 mutations/MB), and TMB was significantly higher in those with deleterious DDR alterations and/or microsatellite instability-high. The most common mutational signature in BTC patients was Signature 1, and interestingly, Signature 1, 4, and 26 was significantly associated with higher TMB level, but not with the survival of patients who had received immunotherapy in pan-cancer. Conclusion: Our study elaborated the distinct germline and somatic genomic characteristics of Chinese BTC patients and identified clinically actionable alterations, highlighting the possibility for the development and application of precision medicine.